Assessment of Single-Bolus Contrast Administration Technique Using Hybrid Dual-Source ECG-Gated Thoracic and Dual-Source Non–ECG-Gated High-Pitch Abdominopelvic CT Acquisitions for Procedural Planning Before Transcatheter Aortic Valve Replacement. Issue 2 (March 2015) - Walker, Wendy L.; Boll, Daniel T.; Bueno, Juliana M.; Kiefer, Todd L.; Vavalle, John P.; Gaca, Jeffrey G.; Harrison, J. Kevin; Hughes, G. Chad; Wang, Andrew; Hurwitz, Lynne M.
<x xml:space="preserve">Abstract</x> Purpose This study aimed to assess vascular contrast opacification and homogeneity using single-bolus contrast administration with hybrid thoracic and abdominopelvic computed tomographic angiography in patients with severe aortic valve stenosis. Materials and Methods Combination electrocardiogram-gated thoracic and dual-source, high-pitch abdominopelvic computed tomographic angiography examinations of 50 patients with severe aortic stenosis between December 2013 and March 2014 were reviewed. Contrast administration was individualized to patient-specific physiology. Image analysis of vascular opacification was obtained and interdependencies of vascular contrast and homogeneity of contrast distribution were assessed. Results The mean volume of contrast administered was 106 ± 11.7 mL. Mean attenuation was 371 ± 90.7 Hounsfield units (HU) in the thoracic aorta and 388 ± 95.9 HU in the abdominal aorta. Homogeneous opacification was obtained throughout with coefficient of variation of 11%. Conclusions Procedural planning for transcatheter aortic valve replacement can be achieved using a single-injection bolus contrast protocol in combination with a 2-part multidetector computed tomographic image acquisition technique with optimal opacification of major arterial structures.